2022
DOI: 10.1155/2022/7646361
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Propofol plus Remifentanil for PostoperativePain and Heart Rate Management in Patients Undergoing Abdominal Hysterectomy

Abstract: Purpose. To explore the effect of propofol plus remifentanil for postoperative pain and heart rate management in patients undergoing abdominal hysterectomy. Methods. In this prospective randomized controlled study, 96 patients who underwent abdominal hysterectomy in an affiliated hospital of Fujian Medical University from April 2016 to April 2017 were recruited and randomized into the study group (n = 48) and control group (n = 48) via the random number table method. The control group received remifentanil for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%